UHD급 영상구현을 위한 다층인쇄회로기판의 특성 임피던스 분석에 관한 연구 - 진종호(Jong-Ho Jin); 손희배(Hui-Bae Son); 이영철(Young-Chul Rhee) (한국정보통신학회논문지, 2015)
In UHD high-speed video transmission system, when a signal within certain frequency region coincides electrically and structurally, the system becomes unstable because the energy is concentrated, and signal flux is interfered and distorted. For the instability, power integrity analysis should be conducted. To remove the signal distortion for MLB, using a high-frequency design technique for EMI phenomenon, EMI which radiates electromagnetic energy fluxed into power layer was analyzed considering system stabilization. In this paper, we proposed an adaptive MLB design method which minimizes high-frequency noise in MLB structure, enhances signal integrity and power integrity, and suppresses EMI. The characteristic impedance for multi-layer circuit board proposed in this study were High-Speed Video Differential Signaling(HSVDS) line width w = 0.203, line gap d = 0.203, beta layer height h = 0.145, line thickness t = 0.0175, dielectric constant εr = 4.3, and characteristic impedance Zdiff = 100.186Ω. When high-speed video differential signal interface board was tested with optimized parameters, the magnitude of Eye diagram output was 672mV, jittering was 6.593ps, transmission frequency was 1.322GHz, signal to noise was 29.62dB showing transmission quality improvement of 10dB compared to previous system. UHD 고속영상 전송 시스템에서 EMI 특성은 특정 주파수 대역의 신호가 전기적, 구조적으로 주파수가 일치될 때, 에너지가 집중되고 신호의 흐름을 방해하여 왜곡이 발생하므로 시스템이 불안정해지는 원인이 된다. 이러한 신호의 왜곡을 제거하기 위하여 전원 무결성 분석과 EMI 현상에 대한 고주파 설계기법이 요구되어진다. 따라서 본 논문에서는 다층인쇄회로기판(MLB : Multi-Layer Printed Circuit Board) 구조에서 발생하는 고주파 잡음을 최소화하고 신호 무결성과 전원 무결성을 개선하면서 EMI를 억제하는 최적의 MLB 설계방법을 제안한다. 제안한 MLB의 특성 임피던스 파라미터는 비유전율 εr = 4.3, 고속영상 차동신호(HSVDS : High-Speed Vih = 0.145deo Differential Signaling)의 선로 폭 w = 0.203, 패턴의 간격 d = 0.203, 패턴의 두께 t = 0.0175, 베타층 위의 높이 를 고려하여 특성 임피던스 Zdiff = 100.186Ω으로 설계하였다. 실험결과 아이패턴의 출력 크기가 672mV, 지터는 6.593ps, 전송 주파수가 1.322GHz, 신호 대 잡음비는 29.62dB로 전송 품질이 개선 전보다 약 10dB 향상 되었다.